Spatiotemporal Restriction of FUSCA3 Expression by Class I BPCs Promotes Ovule Development and Coordinates Embryo and Endosperm Growth. Issue 6 (7th April 2020) - Wu, Jian; Mohamed, Deka; Dowhanik, Sebastian; Petrella, Rosanna; Gregis, Veronica; Li, Jingru; Wu, Lin; Gazzarrini, Sonia
Abstract : Class I BPCs repress FUSCA3 during reproductive and seed development to promote ovule development while coordinating embryo and endosperm growth. Abstract: Spatiotemporal regulation of gene expression is critical for proper developmental timing in plants and animals. The transcription factor FUSCA3 (FUS3) regulates developmental phase transitions by acting as a link between hormonal pathways in Arabidopsis ( Arabidopsis thaliana ). However, the mechanisms governing its spatiotemporal expression pattern are poorly understood. Here, we show that FUS3 is repressed in the ovule integuments and seed endosperm. FUS3 repression requires class I BASIC PENTACYSTEINE (BPC) proteins, which directly bind GA/CT cis -elements in FUS3 and restrict its expression pattern. During vegetative and reproductive development, FUS3 derepression in bpc1-1 bpc2 ( bpc1/2 ) double mutant or misexpression in ProML1:FUS3 lines causes dwarf plants carrying defective flowers and aborted ovules. After fertilization, ectopic FUS3 expression in bpc1/2 endosperm or ProML1:FUS3 endosperm and endothelium increases endosperm nuclei proliferation and seed size, causing delayed or arrested embryo development. These phenotypes are rescued in bpc1/2 fus3-3 . Finally, class I BPCs interact with FIS-PRC2 (FERTILIZATION-INDEPENDENT SEED-Polycomb Repressive Complex2), which represses FUS3 in the endosperm during early seed development. We propose that BPC1 and 2 promote the transition from reproductive to seed development by repressing FUS3 in ovule integuments. After fertilization, BPC1 and 2 and FIS-PRC2 repress FUS3 in the endosperm to coordinate early endosperm and embryo growth.